The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1590/fst.10518
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impacts of the consumers’ awareness of organic food on consumption behavior

Abstract: Consumer demand for organic foods has increased significantly in recent years in the world. Consumers are influenced by various internal/external factors when purchasing food products. The aim of this study is to determine the effects of knowledge variable on consumers' purchasing or consuming behavior for organic foods together with other factors in Turkey (Hatay City). For this purpose, the effects of consumers' organic product knowledge levels are examined within the frame of Theory of Planned Behavior. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 36 publications
(86 reference statements)
3
47
0
4
Order By: Relevance
“…Dn the other hand, they demonstrate the high level of awareness of the respondents regarding organic foods. The degree of knowledge of the population can reinforce the consumption trend and consequently increase the interest to purchase, the willingness to pay more and increase the consumption frequency, since increasing consumer awareness about the benefits certain foods have stimulates their acquisition (Lee & Yun, 2015), meaning that the more benefits perceived, the greater the intent to consume (Demirtas, 2018;Yazdanpanah et al, 2015).…”
Section: Consumers Degree Of Knowledge About Organic Foodmentioning
confidence: 99%
“…Dn the other hand, they demonstrate the high level of awareness of the respondents regarding organic foods. The degree of knowledge of the population can reinforce the consumption trend and consequently increase the interest to purchase, the willingness to pay more and increase the consumption frequency, since increasing consumer awareness about the benefits certain foods have stimulates their acquisition (Lee & Yun, 2015), meaning that the more benefits perceived, the greater the intent to consume (Demirtas, 2018;Yazdanpanah et al, 2015).…”
Section: Consumers Degree Of Knowledge About Organic Foodmentioning
confidence: 99%
“…The literature shows that, in general, attitudes are a solid antecedent of purchase intention. In reference to green products, Honkanen et al [65] and Demirtas [66], among others, have shown a significant positive relationship between attitudes toward green products and the intention to purchase these products. Nevertheless, for certain aspects that are strongly related to attitudes, different relationships have been found.…”
Section: Explicit Attitudes Toward Green Products and The Purchase Ofmentioning
confidence: 98%
“…The survey used in this research consisted of a total number of 29 questions with at least two questions (items) being allocated to each of the previously described constructs. The items were confirmed through the research of Ashraf et al (2019), Demirtas (2019) and Emekci (2019). The survey closed with four questions regarding the demographics of the respondents and a comment box for open-ended feedback.…”
Section: Survey and Itemsmentioning
confidence: 98%
“…In the original TPB model, Ajzen 1991 stated that positive attitudes towards a product lead to a more favourable evaluation of the product by the consumer. Attitudes develop from an individual's belief about what performing a certain act (Fishbein and Ajzen, 1975) means, and similarly to subjective norms, are formed by the social environment, health concerns, product quality, the environmental knowledge and consciousness of the individual consumer (Demirtas, 2019) and the experiences any consumer has and makes throughout life. Attitudes can be both positive and negative but it is presumed that a more positive attitude towards a product leads to a higher likelihood of the positive consequences of an engagement in purchasing intention.…”
Section: Attitudesmentioning
confidence: 99%